Functional interaction between APOE4 and LDL receptor isoforms in Alzheimer's disease. Issue 2 (2nd February 2005) - Cheng, D; Huang, R; Lanham, I S; Cathcart, H M; Howard, M; Corder, E H; Poduslo, S E
Abstract : Background: Multiple genes have been provisionally associated with Alzheimer's disease, including the coding polymorphisms in exons 8 and 13 in the low density lipoprotein receptor gene (LDLR), situated on chromosome 19p13.2. Methods: The sample groups consisted of 180 AD patients and 141 control spouses. We carried out genotyping of LDLR8 and LDLR13. Results: The LDLR8 GG genotype was common, found in 84% of the unaffected control subjects and 91% of the AD patients in our study. There was a ninefold elevation in risk associated with GG:CC versus A– and T– among APOE4+ subjects when compared with APOE4− subjects (odds ratio 9.3; 95% confidence interval 1.8 to 48.2). With the additional information on LDLR polymorphism, we defined an overall 12 fold elevation in risk for APOE4 in combination with LDLR GG:CC (11.9; 2.8 to 50.0; Fisher's exact test, p = 0.0002; standard power 0.999), compared with other subjects lacking all three of these polymorphisms. Conclusion: These results imply a functional interaction between ApoE and LDL receptor proteins that determines risk for Alzheimer's disease.